Pengaruh Penggunaan Aplikasi Keretaku dan Kualitas Pelayanan terhadap Minat Penggunaan Jasa di PT Adi Dharma Rantauprapat - Camna Ritonga; Basyarul Ulya; Jeni Sukmal (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the influence of Keretaku application usage and service quality on customer interest in utilizing services at PT Adi Dharma Rantauprapat. A quantitative approach was employed using multiple linear regression analysis to assess the impact of the two independent variables Keretaku application usage and service quality on the dependent variable, which is customer interest. Data were collected through questionnaires distributed to 100 respondents, all of whom are active customers of the company. The findings indicate that both independent variables significantly affect customer interest. The use of the Keretaku application demonstrated a stronger impact with a regression coefficient of 0.437 and a p-value of 0.000, indicating a highly significant influence. Service quality also contributed significantly, with a regression coefficient of 0.319 and a p-value of 0.000. The coefficient of determination (R²) was found to be 0.321, meaning that 32.1% of the variation in customer interest can be explained by the two independent variables. These results highlight the importance of technological adoption and service quality enhancement in fostering customer loyalty and sustained service interest. Therefore, PT Adi Dharma Rantauprapat is advised to continuously improve relevant features in the Keretaku application and maintain high service standards to strengthen its competitive advantage in the service industry.